Mosaic variants in the LIM homeobox 1 (LHX1) gene contribute to Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome - Dina Kira; Soumia Brakta; Hyung Goo Kim; Jennifer Butler; Lynn P. Chorich; John A. Phillips; Lawrence C. Layman (Human Genetics, 2026)

Storm surge-driven salinization mechanisms in coastal aquifers: Insights from 2D and 3D modelling in southwestern Bangladesh - ChiSan Tsai; Sean E. Feist; Mohammad A. Hoque; Kazi Matin Ahmed; Adrian P. Butler (Advances in Water Resources, 2026)

Investigating reservoir-scale heterogeneity in Li-enriched oil field brines of the Devonian Leduc and Nisku formations, Alberta Basin, Canada - M.R. Blake; K.L. Butler; L.A. Munk; D.F. Boutt; N. Morris; J. Kennedy; P. Saha; J. Serotta; H. Tompkins; G. Williams; A. Vengosh; J. Evaristo; et al. (Applied Geochemistry, 2026)

Effects of environmental conditions on mate fidelity in a socially monogamous seabird - Sue Lewis; Adam Butler; Sarah Wanless; Mark A. Newell; Michael P. Harris; Sarah J. Burthe; Carrie M. Gunn; Richard J. Howells; Francis Daunt (Animal Behaviour, 2025)

Exotic plant responses to large-scale commercial logging in ponderosa pine forests of the Black Hills National Forest, South Dakota, USA - Jack L. Butler; Stefanie D. Wacker; Jacqueline P. Ott; Scott Baggett; Michael A. Battaglia (Forest Ecology and Management, 2025)

Time-lapse resistivity imaging and self-potential monitoring of experimentally induced saline intrusion in coastal aquifer sands - Jesús F. Águila; Thomas S.L. Rowan; Mark C. McDonnell; Raymond Flynn; Shane Donohue; Matthew D. Jackson; Adrian P. Butler; Gerard A. Hamill; Eric M. Benner; Georgios Etsias (Science of The Total Environment, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Double-blind, Randomized, Placebo-controlled Crossover Study Evaluating Reducose® Mulberry Leaf Extract at 3 Levels Shows Significant Effects on Postprandial Blood Glucose and Insulin After Eating a Complex Meal - B. Davis; P. Thondre; J. Tammam; I. Butler; M. Lane; A. Gallagher (Journal of the Academy of Nutrition and Dietetics, 2024)

The origin and water quality of spring systems in Monchique, Portugal: A focus on Long-Term sustainability and elevated sodium levels - M.A. Hoque; K.B. Amponsah; A. Blum; N. Walton; P. Dennis; A.P. Butler; S. Hugman; A. Bamberger; M. Fowler (Journal of Hydrology, 2024)

Controls on timescales of soil organic carbon persistence across sub‐Saharan Africa - Sophie F. von Fromm; Sebastian Doetterl; Benjamin M. Butler; Ermias Aynekulu; Asmeret Asefaw Berhe; Stephan M. Haefele; Steve P. McGrath; Keith D. Shepherd; Johan Six; Lulseged Tamene; Ebagnerin J. Tondoh; Tor‐Gunnar Vågen; et al. (Global Change Biology, 2024)
Given the importance of soil for the global carbon cycle, it is essential to understand not only how much carbon soil stores but also how long this carbon persists. Previous studies have shown that the amount and age of soil carbon are strongly affected by the interaction of climate, vegetation, and mineralogy. However, these findings are primarily based on studies from temperate regions and from fine‐scale studies, leaving large knowledge gaps for soils from understudied regions such as sub‐Saharan Africa. In addition, there is a lack of data to validate modeled soil C dynamics at broad scales. Here, we present insights into organic carbon cycling, based on a new broad‐scale radiocarbon and mineral dataset for sub‐Saharan Africa. We found that in moderately weathered soils in seasonal climate zones with poorly crystalline and reactive clay minerals, organic carbon persists longer on average (topsoil: 201 ± 130 years; subsoil: 645 ± 385 years) than in highly weathered soils in humid regions (topsoil: 140 ± 46 years; subsoil: 454 ± 247 years) with less reactive minerals. Soils in arid climate zones (topsoil: 396 ± 339 years; subsoil: 963 ± 669 years) store organic carbon for periods more similar to those in seasonal climate zones, likely reflecting climatic constraints on weathering, carbon inputs and microbial decomposition. These insights into the timescales of organic carbon persistence in soils of sub‐Saharan Africa suggest that a process‐oriented grouping of soils based on pedo‐climatic conditions may be useful to improve predictions of soil responses to climate change at broader scales.

Pectin as a biopolymer source for packaging films using a circular economy approach: Origins, extraction, structure and films properties - Ian P. Butler; Russell A. Banta; Andrey A. Tyuftin; Justin Holmes; Shivani Pathania; Joe Kerry (Food Packaging and Shelf Life, 2023)

Effects of a fishery closure and prey abundance on seabird diet and breeding success: Implications for strategic fisheries management and seabird conservation - Kate R. Searle; Charlotte E. Regan; Martin R. Perrow; Adam Butler; Anna Rindorf; Michael P. Harris; Mark A. Newell; Sarah Wanless; Francis Daunt (Biological Conservation, 2023)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

Towards open-source LOD2 modelling using convolutional neural networks - H. Muftah; T. S. L. Rowan; A. P. Butler (Modeling Earth Systems and Environment, 2022)
The aim of this paper is to classify and segment roofs using vertical aerial imagery to generate three-dimensional (3D) models. Such models can be used, for example, to evaluate the rainfall runoff from properties for rainwater harvesting and in assessing solar energy and roof insulation options. Aerial orthophotos and building footprints are used to extract individual roofs and bounding boxes, which are then fed into one neural network for classification and then another for segmentation. The approach initially implements transfer learning on a pre-trained VGG16 model. The first step achieves an accuracy of 95.39% as well as a F 1 score of 95%. The classified images are segmented using a fully convolutional network semantic segmentation model. The mask of the segmented roof planes is used to extract the coordinates of the roof edges and the nexus points using the Harris corner detector algorithm. The coordinates of the corners are then used to plot a 3D Level of Detail 2 (LOD2) representation of the building and the roof height is determined by calculating the maximum and minimum height of a Digital Surface Model LiDAR point cloud and known building height data. Subsequently the wireframe plot can be used to compute the roof area. This model achieved an accuracy of 80.2%, 96.1%, 96.0%, 85.1% and 91.1% for flat, hip, gable, cross-hip and mansard roofs, respectively.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Adipose derived stem cells and platelet rich plasma improve the tissue integration and angiogenesis of biodegradable scaffolds for soft tissue regeneration - N. Naderi; M. F. Griffin; A. Mosahebi; P. E. Butler; A. M. Seifalian (Molecular Biology Reports, 2020)
Current surgical reconstruction for soft tissue replacement involves lipotransfer to restore soft tissue replacements but is limited by survival and longevity of the fat tissue. Alternative approaches to overcome these limitations include using biodegradable scaffolds with stem cells with growth factors to generate soft tissue. Adipose derived stem cells (ADSCs) offer great potential to differentiate into adipose, and can be delivered using biodegradable scaffolds. However, the optimal scaffold to maximise this approach is unknown. This study investigates the biocompatibility of nanocomposite scaffolds (POSS-PCL) to deliver ADSCs with and without the addition of growth factors using platelet rich plasma (PRP) in vivo. Rat ADSCs were isolated and then seeded on biodegradable scaffolds (POSS-PCL). In addition, donor rats were used to isolate PRP to modify the scaffolds. The implants were then subcutaneously implanted for 3-months to assess the effect of PRP and ADSC on POSS-PCL scaffolds biocompatibility. Histology after explanation was examined to assess tissue integration (H&E) and collagen production (Massons Trichome). Immunohistochemistry was used to assess angiogenesis (CD3, α-SMA), immune response (CD45, CD68) and adipose formation (PPAR-γ). At 3-months PRP-ADSC-POSS-PCL scaffolds demonstrated significantly increased tissue integration and angiogenesis compared to PRP, ADSC and unmodified scaffolds (p < 0.05). In addition, PRP-ADSC-POSS-PCL scaffolds showed similar levels of CD45 and CD68 staining compared to unmodified scaffolds. Furthermore, there was increased PPAR-γ staining demonstrated at 3-months with PRP-ADSC-POSS-PCL scaffolds (p < 0.05). POSS-PCL nanocomposite scaffolds provide an effective delivery system for ADSCs. PRP and ADSC work synergistically to enhance the biocompatibility of POSS-PCL scaffolds and provide a platform technology for soft tissue regeneration.

Impact of Climate Change and Land Use on Groundwater Salinization in Southern Bangladesh—Implications for Other Asian Deltas - M. A. Islam; M. A. Hoque; K. M. Ahmed; A. P. Butler (Environmental Management, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Correction to: Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Pronounced long-term trends in year-round diet composition of the European shag Phalacrocorax aristotelis - Richard J. Howells; Sarah J. Burthe; Jonathan A. Green; Michael P. Harris; Mark A. Newell; Adam Butler; Sarah Wanless; Francis Daunt (Marine Biology, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Vulnerability of forests of the Midwest and Northeast United States to climate change - Chris Swanston; Leslie A. Brandt; Maria K. Janowiak; Stephen D. Handler; Patricia Butler-Leopold; Louis Iverson; Frank R. Thompson III; Todd A. Ontl; P. Danielle Shannon (Climatic Change, 2018)

Adaptation pathways: ecoregion and land ownership influences on climate adaptation decision-making in forest management - Todd A. Ontl; Chris Swanston; Leslie A. Brandt; Patricia R. Butler; Anthony W. D’Amato; Stephen D. Handler; Maria K. Janowiak; P. Danielle Shannon (Climatic Change, 2018)

Biomechanical Characterisation of the Human Auricular Cartilages; Implications for Tissue Engineering - M. F. Griffin; Y. Premakumar; A. M. Seifalian; M. Szarko; P. E. M. Butler (Annals of Biomedical Engineering, 2016)

Drinking water vulnerability to climate change and alternatives for adaptation in coastal South and South East Asia - M. A. Hoque; P. F. D. Scheelbeek; P. Vineis; A. E. Khan; K. M. Ahmed; A. P. Butler (Climatic Change, 2016)

Trends in marine climate change research in the Nordic region since the first IPCC report - M. W. Pedersen; A. Kokkalis; H. Bardarson; S. Bonanomi; W. J. Boonstra; W. E. Butler; F. K. Diekert; N. Fouzai; M. Holma; R. E. Holt; K. Ø. Kvile; E. Nieminen; et al. (Climatic Change, 2016)

Integrating Top-Down and Bottom-Up Adaptation Planning to Build Adaptive Capacity: A Structured Learning Approach - J. R. A. Butler; R. M. Wise; T. D. Skewes; E. L. Bohensky; N. Peterson; W. Suadnya; Y. Yanuartati; T. Handayani; P. Habibi; K. Puspadi; N. Bou; D. Vaghelo; et al. (Coastal Management, 2015)

Age and growth of mangrove red snapper Lutjanus argentimaculatus at its cool‐water‐range limits - T. P. Piddocke; G. L. Butler; P. A. Butcher; J. Stewart; D. J. Bucher; L. Christidis (Journal of Fish Biology, 2015)
This study investigates the age and growth of Lutjanus argentimaculatus at its southern (cooler) range limits in eastern Australia. Specimens were collected from New South Wales and southern Queensland between November 2011 and December 2013. Fork lengths ( L F ) ranged from 190 to 1019 mm, and ages ranged from 2+ to 57+ years. Growth was described by the von Bertalanffy growth function with coefficients L ∞ = 874·92 mm, K = 0·087 year −1 and t 0 = −2·76 years. Estimates of the instantaneous natural mortality rate ( M ) ranged from 0·072 to 0·25. The L F (mm) and mass ( W ; g) relationship was represented by the equation: . The maximum age of 57+ years is the oldest reported for any lutjanid and comparisons with tropical studies suggest that the age‐based demography of L. argentimaculatus follows a latitudinal gradient. High maximum ages and low natural mortality rates indicate considerable vulnerability to overexploitation at the species' cool‐water‐range limits. These results demonstrate the need to identify underlying processes driving latitudinal gradients in fish demography.

Compounds alone and in combination with yeasts to control Colletotrichum acutatum in apples - Kirsty S. H. Boyd-Wilson; Ruth C. Butler; Peter A. Alspach; Kerry R. Everett; I. P. Shamini Pushparajah; Monika Walter (Australasian Plant Pathology, 2014)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Soil organic carbon dust emission: an omitted global source of atmospheric CO 2 - Adrian Chappell; Nicholas P. Webb; Harry J. Butler; Craig L. Strong; Grant H. McTainsh; John F. Leys; Raphael A. Viscarra Rossel (Global Change Biology, 2013)
Soil erosion redistributes soil organic carbon ( SOC ) within terrestrial ecosystems, to the atmosphere and oceans. Dust export is an essential component of the carbon (C) and carbon dioxide ( CO 2 ) budget because wind erosion contributes to the C cycle by removing selectively SOC from vast areas and transporting C dust quickly offshore; augmenting the net loss of C from terrestrial systems. However, the contribution of wind erosion to rates of C release and sequestration is poorly understood. Here, we describe how SOC dust emission is omitted from national C accounting, is an underestimated source of CO 2 and may accelerate SOC decomposition. Similarly, long dust residence times in the unshielded atmospheric environment may considerably increase CO 2 emission. We developed a first approximation to SOC enrichment for a well‐established dust emission model and quantified SOC dust emission for Australia (5.83 Tg CO 2 ‐e yr −1 ) and Australian agricultural soils (0.4 Tg CO 2 ‐e yr −1 ). These amount to underestimates for CO 2 emissions of ≈10% from combined C pools in Australia (year = 2000), ≈5% from Australian Rangelands and ≈3% of Australian Agricultural Soils by Kyoto Accounting. Northern hemisphere countries with greater dust emission than Australia are also likely to have much larger SOC dust emission. Therefore, omission of SOC dust emission likely represents a considerable underestimate from those nations’ C accounts. We suggest that the omission of SOC dust emission from C cycling and C accounting is a significant global source of uncertainty. Tracing the fate of wind‐eroded SOC in the dust cycle is therefore essential to quantify the release of CO 2 from SOC dust to the atmosphere and the contribution of SOC deposition to downwind C sinks.

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Switchgrass Biomass and Nitrogen Yield with Over-Seeded Cool-season Forages in the Southern Great Plains - Twain J. Butler; James P. Muir; Chengjun Huo; John A. Guretzky (BioEnergy Research, 2013)

Soil warming alters nitrogen cycling in a New England forest: implications for ecosystem function and structure - S. M. Butler; J. M. Melillo; J. E. Johnson; J. Mohan; P. A. Steudler; H. Lux; E. Burrows; R. M. Smith; C. L. Vario; L. Scott; T. D. Hill; N. Aponte; et al. (Oecologia, 2012)

Generation of antibody- and B cell-deficient pigs by targeted disruption of the J-region gene segment of the heavy chain locus - M. Mendicino; J. Ramsoondar; C. Phelps; T. Vaught; S. Ball; T. LeRoith; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; et al. (Transgenic Research, 2011)

Targeted disruption of the porcine immunoglobulin kappa light chain locus - J. Ramsoondar; M. Mendicino; C. Phelps; T. Vaught; S. Ball; J. Monahan; S. Chen; A. Dandro; J. Boone; P. Jobst; A. Vance; N. Wertz; et al. (Transgenic Research, 2011)

A New Generation Fatty Acid Amide Hydrolase Inhibitor Protects Against Kainate-Induced Excitotoxicity - Vinogran Naidoo; Spyros P. Nikas; David A. Karanian; Jeannie Hwang; Jianhong Zhao; JodiAnne T. Wood; Shakiru O. Alapafuja; Subramanian K. Vadivel; David Butler; Alexandros Makriyannis; Ben A. Bahr (Journal of Molecular Neuroscience, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Improving the Performance of the Roundtable on Sustainable Palm Oil for Nature Conservation - WILLIAM F. LAURANCE; LIAN P. KOH; RHETT BUTLER; NAVJOT S. SODHI; COREY J. A. BRADSHAW; J. DAVID NEIDEL; HAZEL CONSUNJI; JAVIER MATEO VEGA (Conservation Biology, 2010)

Active, but not passive cigarette smoking was inversely associated with mammographic density - Lesley M. Butler; Ellen B. Gold; Shannon M. Conroy; Carolyn J. Crandall; Gail A. Greendale; Nina Oestreicher; Charles P. Quesenberry; Laurel A. Habel (Cancer Causes & Control, 2010)

Analysis of flow processes in fractured chalk under pumped and ambient conditions (UK) - A. P. Butler; S. A. Mathias; A. J. Gallagher; D. W. Peach; A. T. Williams (Hydrogeology Journal, 2009)

Thinking and managing outside the box: coalescing connectivity networks to build region-wide resilience in coral reef ecosystems - R. S. Steneck; C. B. Paris; S. N. Arnold; M. C. Ablan-Lagman; A. C. Alcala; M. J. Butler; L. J. McCook; G. R. Russ; P. F. Sale (Coral Reefs, 2009)

Tracking macaroni penguins during long foraging trips using ‘behavioural geolocation’ - Jonathan A. Green; Rory P. Wilson; Ian L. Boyd; Anthony J. Woakes; Chris J. Green; Patrick J. Butler (Polar Biology, 2009)

Modelling the impacts of removing seal predation from Atlantic salmon, Salmo salar , rivers in Scotland: a tool for targeting conflict resolution - J. R. A. BUTLER; S. J. MIDDLEMAS; I. M. GRAHAM; P. M. THOMPSON; J. D. ARMSTRONG (Fisheries Management and Ecology, 2006)
Bioenergetics were used to model the potential impacts on adult Atlantic salmon, Salmo salar L., stocks and rod fisheries of removing harbour seals, Phoca vitulina L., from three rivers of different scales in the Moray Firth, Scotland, viz: the Spey (large), Conon (medium) and Moriston (small). Overall, seals had the greatest impact on the Moriston, where removal of a single animal could increase cumulative catch by 17% during the fishing season. On the Conon and Spey the impacts were negligible, and resulted in increased catches of 33% in rivers with monthly rod catches ≤10 fish, but declined to 34 fish. The outputs of the models are qualitative, but provide a management tool for targeting action to resolve seal‐salmon fishery conflict. Smaller salmon population units, and spring salmon sub‐stocks and fisheries in particular, are most vulnerable to predation. The merit of this approach is discussed regarding the management of Special Areas of Conservation for salmon and seals.

Accounting for body condition improves allometric estimates of resting metabolic rates in fasting king penguins, Aptenodytes patagonicus - A. Fahlman; L. G. Halsey; P. J. Butler; D.R. Jones; A. Schmidt; S. Durand; G. Froget; C. -A. Bost; A. J. Woakes; C. Duchamp; Y. Handrich (Polar Biology, 2006)

Free-range Village Chickens on the Accra Plains, Ghana:Their Husbandry and Productivity - P. A. T. Aboe; K. Boa-Amponsem; S. A. Okantah; E. A. Butler; P. T. Dorward; M. J. Bryant (Tropical Animal Health and Production, 2006)

Inhibitory Effect of a Herbicide Formulation on Toxicity of Malathion to the Worm Eisenia fetida - D. W. Butler; P. A. Verrell (Bulletin of Environmental Contamination and Toxicology, 2005)

The prevalence of escaped farmed salmon, Salmo salar L., in the River Ewe, western Scotland, with notes on their ages, weights and spawning distribution - J. R. A. BUTLER; P. D. CUNNINGHAM; K. STARR (Fisheries Management and Ecology, 2005)
The prevalence of escaped farmed Atlantic salmon, Salmo salar L., in the River Ewe, western Scotland, was assessed. After the establishment of smolt cages in the catchment and marine cages near the river mouth during 1986–1987, approximately 425 000 parr and smolts, and 122 000 growers have escaped. Between 1987 and 2001, farmed salmon occurred in the rod fishery in 13 of the 15 years, contributing at least 5.8% of the total catch, with a maximum annual frequency of 27.1%. It was estimated that P

Effects of dietary supplementation with vitamins C and E on muscle function during and after eccentric contractions in humans - A. Shafat; P. Butler; R. L. Jensen; A. E. Donnelly (European Journal of Applied Physiology, 2004)

Reduced metaphase I associations between the short arms of homoeologous chromosomes in a Hordeum vulgare L. H. bulbosum L. diploid hybrid influences the frequency of recombinant progeny - R. A. Pickering; S. Hudakova; A. Houben; P. A. Johnston; R. C. Butler (Theoretical and Applied Genetics, 2004)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

s of papers presented at the Forty-First annual meeting - R. E. Anderson; A. P. Benson; W. J. Hooker; Gerard S. Birth; Karl H. Norris; Reiner Bonde; Robert Akeley; Donald Merriam; C. C. Craft; H. W. Siegelman; W. L. Butler; L. A. Dionne; et al. (American Journal of Potato Research, 1958)